2021
DOI: 10.7150/ijms.56551
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs may impact podocytes and proximal tubule function through modulating miRNAs expression in Early Diabetic Kidney Disease of Type 2 Diabetes Mellitus patients

Abstract: Aims: Long noncoding RNAs (lncRNAs) play key roles in the pathophysiology of DKD involving actions of microRNAs (miRNAs). The aims of the study were to establish the involvement of selected lncRNAs in the epigenetic mechanisms of podocyte damage and tubular injury in DKD of type 2 diabetes mellitus (DM) patients in relation to a particular miRNAs profile. Methods: A total of 136 patients with type 2 DM and 25 healthy subjects were assessed in a cross-sectional study concernin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…Metastasis-associated lung adenocarcinoma transcript 1, also known as Neat2 (Malat1) is one of the most analyzed lncRNAs in DKD samples. The qualitative analysis showed that lncRNAs were expressed in serum, urine, peripheral blood mononuclear cells, and kidney tissue [ 29 , 30 , 36 , 37 , 39 ]. There were increased expressions of lncRNA MALAT1 in DKD, translocation of β -catenin to the nucleus, enhanced expressions of MALAT1 connexin serine/arginine splicing factor 1 (SRSF1), and expressions of p-cadherin and tight junction protein ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis-associated lung adenocarcinoma transcript 1, also known as Neat2 (Malat1) is one of the most analyzed lncRNAs in DKD samples. The qualitative analysis showed that lncRNAs were expressed in serum, urine, peripheral blood mononuclear cells, and kidney tissue [ 29 , 30 , 36 , 37 , 39 ]. There were increased expressions of lncRNA MALAT1 in DKD, translocation of β -catenin to the nucleus, enhanced expressions of MALAT1 connexin serine/arginine splicing factor 1 (SRSF1), and expressions of p-cadherin and tight junction protein ZO-1.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of physiology and pathology, various research groups determined NEAT1 as a prognosis marker for poor survival rates and promoter of tumorigenesis [ 28 , 29 , 30 ]. With regard to DKD, others showed a positive and negative correlation, respectively, between elevated urinary NEAT1 and various podocyte damage markers like synaptopodin and podocalyxin or GFR [ 42 ]. HG-exposed proximal tubular cells (HK-2) or murine MCs (mMCs) exhibited an increase in NEAT1 expression in a dose- or time- dependent manner [ 31 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recent advances in finding biomarkers of early DKD in diabetic population by omics and molecular-biology also supplied an alternative method. For instance, long noncoding RNAs (lncRNAs) have been suggested to play a role in early development of DKD [ 18 ], and glycated peptides within the urine may predict dysfunction of proximal tubule within the kidney [ 19 ].…”
Section: Discussionmentioning
confidence: 99%